Leprosy for medical practitioners and paramedical workers - Yawalkar, S. J.; Novartis Foundation for Sustainable Development (Basle, Switzerland : Novartis Foundation for Sustainable Development, 1992)
When the first edition of this book was published in 1987, leprosy was still a public health problem in 122 countries. The global number of patients was estimated at between 10 million and 12 million. In the past, leprosy was, and in some places continues to be, a stigmatized disease, and those affected were isolated in leprosaria or segregated villages for fear of infection. As a consequence of prejudice and lack of knowledge, leprosy patients were ashamed of their condition and tried to hide the disease -- their only way to escape social repercussions. The consequent lack of treatment or delayed treatment resulted in an increased risk of disabilities, which in turn strengthened and perpetuated the stigma of the disease -- a vicious circle. The development of multidrug therapy (MDT) changed the face of leprosy dramatically. The treatment consists of three drugs, two of which were developed in the research laboratories of Novartis. MDT made it possible to cure patients, interrupt the transmission of leprosy, and thus -- most important for the social perception of the illness -- prevent disabilities. Even patients with the severest form of the disease show visible clinical improvement within weeks of starting treatment. In 1981, the World Health Organization (WHO) recommended MDT as the standard treatment against leprosy.
Includes bibliographical references.
Keywords: Epidemics; Leprosy; Leprosy